2007
DOI: 10.1007/s10048-007-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of shared risk for Alzheimer’s disease and Parkinson’s disease using family history

Abstract: This case-control study examined the potential for a common etiology of Parkinson's disease (PD) and Alzheimer's disease (AD) using reported family history. Structured interviews were used to collect AD and PD family history from subjects (n=1531) with AD, PD, AD/PD, or controls. Intergroup analysis compared reported AD and PD family histories in the three case groups to the histories reported in the control group. Intragroup analysis stratified each diagnostic group based on positive family history of AD, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…10 In our study, a firstdegree family history of PD was more common in DLB compared with AD and normal control subjects. It is not known whether these relatives also had accompanying dementia.…”
Section: Resultsmentioning
confidence: 43%
See 2 more Smart Citations
“…10 In our study, a firstdegree family history of PD was more common in DLB compared with AD and normal control subjects. It is not known whether these relatives also had accompanying dementia.…”
Section: Resultsmentioning
confidence: 43%
“…The results likely reflect the mixed synuclein/AD pathology seen in most DLB cases. The presence of one or more APOE e4 alleles is a well-known risk factor for AD 10 but it is unrelated to PD. 19 Studies indicate that the risk of PD, 19 and possibly AD, 20 is reduced among coffee and caffeine users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another hospital-based study found no increased risk of Alzheimer's disease in relatives of PD cases without dementia compared to controls [580]. Yet another hospital-based study reported higher frequency of family history of PD in PD cases with family history of Alzheimer's disease compared to PD cases without family history of Alzheimer's disease, corresponding to an OR of 1.7 (95% CI 1.1-2.6) [581].…”
Section: Dementiamentioning
confidence: 96%
“…Of the 16 studies included, 7 investigated the coaggregation of AD and PD as their primary aim [7,16,17,18,19,20,21], whereas 9 studies investigated the coaggregation of AD and PD as one of many aims [6,14,15,22,23,24,25,26,27]. The relative risk estimates from the studies included in the meta-analysis could be divided into 4 groups: (1) reconstructed cohort studies estimating HR with AD or dementia as the outcome [16,17,18,19,20] (n = 5; table 2); (2) case-control studies estimating OR with AD or dementia as the outcome [6,7,21,22,25,26,27] (n = 7; table 2); (3) reconstructed cohort studies estimating OR with PD or parkinsonism as the outcome [23] (n = 1), and (4) case-control studies estimating OR with PD or parkinsonism as the outcome [21,24] (n = 2).…”
Section: Resultsmentioning
confidence: 99%